Cooperative behavior in adolescents: a contribution of empathy and emotional regulation? - Martínez-Velázquez, Eduardo Salvador; Ponce-Juárez, Sandra Pamela; Díaz Furlong, Alfonso; Sequeira, Henrique (Frontiers in Psychology, 2024)
This study aims to identify different levels of empathy and emotional regulation along adolescent years and their relationship with cooperative behavior. Eighty healthy males were divided into four age groups: 20 early adolescents (EA), 20 middle adolescents (MA), 20 late adolescents (LA) and 20 adults (AD). Participants responded to empathic and emotional regulation scales, then were assigned to an unknown partner to perform the prisoner's dilemma paradigm. The statistics analyses allowed to distinguish the groups on the basis of the components making up the two scales: 1) scores on the Perspective Taking (PT) component were higher for AD and LA participants than for MA and EA groups (p < .05); 2) scores on the Personal Distress (PD) component were higher for EA group than for LA and MA groups (p < .05); 3) scores on the GOALS (difficulties engaging in goal-directed behavior) component were higher for MA and EA groups than for AD group (p < .05). Finally, we observed differences between groups (p < .001) with higher number of cooperation responses in AD compared to MA (p < .05), and EA groups (p < .001). The findings suggest that 1) the cooperative behavior changes during the different stages of adolescence, and, interestingly, 2) these changes seem to be related to the development of empathy and emotional regulation components.